Adsorption of Cr(VI) from aqueous solutions by HNO3-purified and chemically activated pyrolytic tire char. Issue 7 (3rd July 2017) - Makrigianni, Vassiliki; Giannakas, Aris; Bairamis, Feidias; Papadaki, Maria; Konstaninou, Ioannis
ABSTRACT: Pyrolytic tire char adsorbents either demineralized by nitric acid (purified char, PC) or activated with KOH-calcination (activated char, AC) were used for Cr(VI) removal from aquatic solutions and studied by adsorption kinetics, isotherms, and thermodynamics. Adsorbent's physicochemical characteristics were studied by several techniques such as X-ray diffraction, porosimetry, scanning electron microscopy, elemental analysis, and Boehm titration. For PC, acid treatment leads partially to a mesoporous structure while for AC, KOH activation creates also a microporosity enhancing the specific surface area at 443 m 2 g −1 . Cr(VI) adsorption onto both adsorbents followed better second-order kinetics and Langmuir isotherm models and it was exothermic (Δ H  < 0) and spontaneous (Δ G  < 0). The maximum Cr(VI) adsorption capacity for AC and PC was 114 and 79.47 mg g −1, respectively, at pH = 4. The present work reveals that AC and PC can be efficient sorbents for the removal of heavy metal ions, contributing both positively to wastewater treatment and waste tire pyrolysis plants. GRAPHICAL ABSTRACT: